2019
DOI: 10.3758/s13414-019-01719-2
|View full text |Cite
|
Sign up to set email alerts
|

Feature-based guidance of attention during post-saccadic selection

Abstract: Current models of trans-saccadic perception propose that, after a saccade, the saccade target object must be localized among objects near the landing position. However, the nature of the attentional mechanisms supporting this process is currently under debate. In the present study, we tested whether surface properties of the saccade target object automatically bias post-saccadic selection using a variant of the visual search task. Participants executed a saccade to a shape-singleton target in a circular array.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
3
6
0
Order By: Relevance
“…This effect has already been replicated and extended to the situation where the color is only an attribute of the object stored in long-term memory (LTM) rather than presented during search (Kerzel & Andres, 2020). Moreover, and in line with our results, objects in a search display matching a completely task-irrelevant color belonging to an object contained in VWM can be saccaded to faster and more accurately for a later second task, even in the absence of a distractor (Hollingworth, Matsukura, & Luck, 2013), and can bias the landing position of saccades in the global effect paradigm (Herwig, Beisert, & Schneider, 2010;Hollingworth et al, 2013), and the accuracy and latency of corrective saccades (Hollingworth & Luck, 2009;Hollingworth & Matsukura, 2019). In two letter report experiments, we could show that a colormatching distractor captures not only the eyes but also covert attention (Foerster & Schneider, 2019).…”
supporting
confidence: 86%
“…This effect has already been replicated and extended to the situation where the color is only an attribute of the object stored in long-term memory (LTM) rather than presented during search (Kerzel & Andres, 2020). Moreover, and in line with our results, objects in a search display matching a completely task-irrelevant color belonging to an object contained in VWM can be saccaded to faster and more accurately for a later second task, even in the absence of a distractor (Hollingworth, Matsukura, & Luck, 2013), and can bias the landing position of saccades in the global effect paradigm (Herwig, Beisert, & Schneider, 2010;Hollingworth et al, 2013), and the accuracy and latency of corrective saccades (Hollingworth & Luck, 2009;Hollingworth & Matsukura, 2019). In two letter report experiments, we could show that a colormatching distractor captures not only the eyes but also covert attention (Foerster & Schneider, 2019).…”
supporting
confidence: 86%
“…This suggests that the allocation of memory resources to the saccade target is obligatory. This automatic allocation could be in the service of transsaccadic integration, but is also consistent with the use of visual working memory to facilitate other perceptual or cognitive processes, e.g., to facilitate visual search (Oh & Kim, 2004;Woodman & Luck, 2004) or attentional shifts after the saccade (Hollingworth & Matsukura, 2019).…”
Section: Introductionsupporting
confidence: 68%
“…Trans-saccadic memory has been considered to be based on visual working memory ( Luck & Vogel, 1997 ), due to the similarities in limited memory capacity as well as the timing duration of a few seconds ( Bays & Husain, 2008 ; Cowan, 2011 ; Irwin, 1992 ; Irwin, 1996 ; Jeyachandra et al, 2018 ; Luck & Vogel, 1997 ). Previous studies have shown evidence for automatic attention leading to automatic encoding into visual working/trans-saccadic memory ( Hollingworth & Matsukura, 2019 ; Jonikaitis & Moore, 2019 ; Kong, Kroell, Schneegans, Aagten-Murphy, & Bays, 2021 ), at the expense of the item already in memory, namely here memory of the pre-saccadic symbol is disrupted, resulting in decreased discrimination performance. The observed disruption of trans-saccadic memory due to post-saccadic changes therefore adds arguments for limited resources in trans-saccadic memory ( Poth et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%